THE LANGUAGE OF LIGHT IN CULTURE: BETWEEN SPIRITUALITY AND PRACTICALITY - Zakaria, Safial Aqbar (Journal of Human Capital Development (JHCD), 2011)
The meaning of light in Malay culture have been understood not only in the scientific and physical senses, but understood more deeply within the culture. This research includes rituals and customs which encompass the philosophy and meanings of light from the Malay interpretation and understandings in terms of culture, spirituality, physical attributes and emotion. The objective of this research is to compare the meaning of light according to the understandings, interpretation and beliefs of the two cultures, the Malays and European. This includes level of spirituality and practicality. The results of this research are mainly qualitative in nature. There are supported by structured interviews, personal observation and visual data to scrutinize the problems and questions raised in this research. The primary result from the in-depth interviews with the architects, lighting designer from Europe and religious experts have been analyzed and helped to answer the issues. The findings from this research reflect the values and essence of the Malay community and manifested in hardcopy, representing a creation of art that symbolises the meaning and spirit of the Malays. It is a cultural identity, social interaction, morality, a symbol, and the contents of culture and race. Light and lighting should also not be understood only in the normal sense of being merely a design or practicality purposes, but it needs to be appreciated and expressed through emotions, mind and body, culture belonging, belief and divinity aspects. Through its existence the appreciation of the humanity and society has been highlighted. Keywords: light culture, spirituality, religious, lighting design, belief.